Molecular Identification, Nutritional Profile and Heavy Metals Content of Edible Caulerpa from Binuangeun Coast, Banten - Sihono Sihono; Bagus Sediadi Bandol Utomo; Nurhayati Nurhayati (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2021)
Two species of Caulerpa, locally known as “Pedesan” and “Latuh” have been traditionally consumed by coastal communities at Binuangeun, Banten. This study aimed to identify “Pedesan” and “Latuh” using the DNA barcoding method and to evaluate their nutrient and heavy metal contents. Fatty acids were determined by Gas Chromatography Flame Ionization Detector (GC FID), amino acids using Ultra Performance Liquid Chromatography (UPLC), and minerals using Inductively Coupled Plasma Optical Emission Spectrometry (ICP OES). Based on the tufA gene sequences, the “Pedesan” was identified as Caulerpa racemosa var. macrophysa and “Latuh” as Caulerpa chemnitzia. Thirteen fatty acids were detected in C. racemosa var. macrophysa and twelve fatty acids in C. chemnitzia. Of the total fatty acid content, C. racemosa var. macrophysa contained 41.0% unsaturated fatty acids, dominated by linolenic acid and eicosapentaenoic acid. Meanwhile, C. chemnitzia contained 47.5%, dominated by oleic acid. Both seaweeds contained fatty acids with the w6/w3 ratio lower than 10, which could prevent heart disease risk based on World Health Organization (WHO) recommendation. The primary amino acids content in C. racemosa var. macrophysa were glutamic acid, alanine, serine and aspartic acid, while those in C. chemnitzia were glutamic acid, serine, aspartic acid, and glycine. The high content of glutamic acid in both samples indicated their potential use as food flavor enhancer. The Na/K ratio of C. racemosa var. macrophysa (40.31) and C. chemnitzia (27.48) were higher than those recommended by WHO. Heavy metals were not detected in either “Pedesan” nor “Latuh”, indicating that they are safe for consumption.